Zafirah Meatball Shop Marketing Communication Strategy In Increasing Sales Turnover In Ngronggot Nganjuk City - Kumalaputri, Zairika; Samari (Proceeding Kilisuci International Conference on Economic & Business, 2025)
Research aim : The purpose of this research is to understand the marketing communication strategies commonly used by Warung Bakso Zafirah in promoting its products and increasing sales. Examining the various obstacles faced by Warung Bakso Zafirah related to marketing communication strategies in an effort to increase sales turnover, as well as providing recommendations in overcoming the problems faced. Design/Method/Approach : This research uses a qualitative approach with a descriptive approach. Where this research focuses on collecting information to obtain an understanding or confirmation of a concept or phenomenon and to answer questions related to the current phenomenon being investigated. Data collection techniques by means of interviews, direct observation in the field and documentation Then the informants of this research consist of four sources. Namely the owner or owner of the Zafirah Meatball Warung MSMEs themselves, employees of Zafirah meatball stalls, and buyers or consumers of Zafirah meatball stalls. Research Finding : The results of this study show that there are three marketing communication strategies carried out Marketing strategies at Warung Bakso Zafirah are carried out using the STP (Sagmenthing, Targething, Positioning) marketing mix. Meanwhile, the factors that hinder the communication strategy of Warung Bakso Zafirah in increasing its sales turnover are: The price of staples continues to rise, The number of meatball sellers is also an obstacle, Bad weather conditions such as rain also affect the marketing of Warung Bakso Zafirah Theoretical contribution/Originality : Marketing Communication Strategy is a strategy used to disseminate information, influence/persuade, and remind the target market of the company and its products to be willing to accept, buy and be loyal to the products offered by the company in question. Practitionel/Policy implication : Warung Bakso Zafirah can increase sales turnover by maximizing strategies in marketing their sales, especially in marketing communication strategies, in addition to reaching wider customers, can make the business more advanced and developing. Research limitation : this study only focuses on marketing strategies and factors that hinder the sales  of Warung Bakso Zafirah in increasing sales turnover.